POTRET MODERASI BERAGAMA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MTs AS’ADIYAH ULOE - Syafii, Ahmad; Bulan, Sahri; Hasnawati, Hasnawati; Akmal, Akmal (Balai Diklat Keagamaan Jakarta, 2023)
Abstract Radicalism and intolerance are against Islam and Pancasila. This article describes religious moderation internalization through Islamic Religious Education (PAI) at MTs As'adiyah Uloe, Bone Region South Sulawesi. The research focuses on three aspects: moderation value, methods, media and learning strategies. This research is a qualitative approach that uses the case study method. Data was collected using observation, interview and documentation techniques. Data consist of primary and secondary sources. Preliminary data was taken from interviews and surveys. Secondary data is taken from supporting documents and relevant articles. Data were analyzed using descriptive analysis techniques through the stages of collection, reduction, presentation, drawing conclusions and triangulation. The research formulates several conclusions. Firstly, the value of religious moderation is instilled in intracurricular activities through the subjects of Aqidah Akhlak (tasamuh), Al-Qur'an Hadith (tawazun), Fiqh (tawassuth), and SKI (muwathanah). The extracurricular activities include Al-Qur'an literacy (ta'addub), Duha and Zuhur prayers (musawah); and Saturday Sharing (tasamuh). Secondly, learning methods have lecture, question and answer, discussion and roleplaying. Thirdly, the internalization strategy is carried out through the introduction, implementation, habituation and application stages. Fourthly, the learning media used includes images (pictures), videos, infocus/LCD, and smart TV. Abstrak Radikalisme dan intoleransi sangat bertentangan dengan Islam dan Pancasila. Artikel ini bertujuan untuk mendeskripsikan potret penanaman moderasi beragama di MTs As’adiyah Uloe kecamatan Dua Boccoe Kabupaten Bone Propinsi Sulawesi Selatan. Fokus penelitian meliputi tiga aspek yaitu mutan nilai moderasi pada mata Pelajaran PAI, metode, media dan strategi pembelajaran. Penelitian ini menggunakan pendekatan kualitatif dengan motode studi kasus. Data dikumpulkan menggunakan teknik observasi, wawancara dan dokumentasi. Sumber data terdiri atas sumber primer dan sekunder. Data primer diambil dari hasil wawancara dengan narasumber dan survei terhadap responden. Data sekunder diambil dari arsip atau dokumen penunjang serta artikel yang relevan. Data dianalisis menggunakan teknik analisis deskriptif melalui tahap pengumpulan, reduksi, penyajian, penarikan kesimpulan, dan triangulasi. Penelitian menghasilkan beberapa kesimpulan. Pertama nilai moderasi beragama ditanamkan pada kegiatan intrakurikuler melalui mata Pelajaran Akidah Akhlak (tasamuh), al-Qur’an Hadis (tawazun), Fikih (tawassuth), dan SKI (muwathanah). Adapun dalam kegiatan ekstrakurikuler meliputi Literasi al-Qur’an (ta’addub), salat Duha dan Zuhur berjamaah (musawah); dan Sabtu Berbagi (tasamuh). Kedua, metode pembelajaran meliputi metode ceramah, tanya jawab, diskusi, dan bermain peran. Ketiga, strategi pembelajaran diterapkan melalui tahapan pengenalan, implementasi, habituasi, dan pengaplikasian. Keempat, media pembelajaran yang digunakan meliputi gambar, video, dan infokus/LCD, serta smart tv.